SAT0147 Presence of hepatitis b virus in synovium and its clinical significance in rheumatoid arthritis. (12th June 2018) - Yang, L.-J.; Chen, Y.-L.; Jing, J.; Mo, Y.-Q.; Ma, J.-D.; Chen, L.-F.; Lin, J.-Z.; Yang, Z.-H.; Yan, T.; Zheng, D.-H.; Pessler, F.; Dai, L.
Abstract : Background: Previous studies have shown that hepatitis B virus (HBV) infection may be associated with rheumatoid arthritis (RA). However, no study regarding the presence of HBV in the synovial membrane from RA patients has been reported. Objectives: To investigate the presence of HBV in RA synovium and determine its influence on histopathological characteristics of synovitis as well as clinical and radiographic outcomes in RA. Methods: 57 consecutive patients with active RA (DAS28-CRP≥2.6) and qualified synovium (at least 6 pieces of synovial tissues per patient, containing lining layer and sublining area) obtained by closed Parker-Pearson needle biopsy who had completed one year follow-up were retrospectively recruited from a prospective RA cohort (n=239). The patients were divided into chronic HBV infection (CHB, positive HBsAg and/or HBV DNA in serum persisting for over 6 months; n=11), resolved HBV (negative HBsAg and HBV DNA in serum, but positive anti-HBc; n=22), and non-HBV (negative HBsAg, HBeAg, anti-HBe, anti-HBc, and HBV DNA in serum, regardless of anti-HBs; n=24) groups according to baseline HBV infection status. Clinical data were collected at baseline and follow-up visits at months 1, 3, 6, and 12. Radiographic assessments of hand/wrist at baseline and month 12 were performed with the Sharp/van der Heijde-modified sharp score (mTSS). Serial tissue sections were stained immunohistochemically for HBsAg, HBcAg, CD3, CD15, CD20, CD34, CD38, and CD68. Nested PCR was used to detect HBV S gene DNA in synovium. Results: Immunohistochemical staining and nested PCR revealed the presence of HBcAg and S gene DNA in the synovium from RA patients with CHB (figure 1). Compared with the non-CHB group (n=46), significantly more CD15-positive neutrophils, CD20-positive B cells, and CD68-positive macrophages infiltrated the CHB synovium (all p<0.05), together with smaller improvements from baseline in most disease activity indicators mainly at month 12. A significantly higher percentage of CHB patients experienced one-year radiographic progression (ΔmTSS≥0.5units/year, 64% vs. 26%, p=0.024). Multivariate logistic regression analysis showed that CHB status (OR: 14.230, 95%CI: 2.213–95.388; p=0.006) and the total count of CD68-positive macrophages (OR: 1.002, 95%CI: 1.001–1.003; p=0.003) were independently associated with one-year radiographic progression. Figure 1 Identification of HBV in RA synovium. (A) Representative immunohistochemical staining for HBcAg in RA synovium. Representative images illustrated detection of HBcAg in a RA patient with CHB, but not in RA patients with resolved HBV or no infection. (B) Representative staining of HBcAg in one RA patient with CHB compared to stains for CD38 and CD68. Serial sections of synovium from one RA patient with CHB were stained with H&E and immunohistochemically. HBcAg immunoreactivity was observed in the sublining inflammatory cells including plasma cells (CD38+) and macrophages (CD68+), mainly located in the cytoplasm. (C) Detection of HBV S gene in RA synovium by nested PCR. Nested PCR showed HBV S gene only in all four CHB synovial tissues. Liver tissue from a patient with HBV-related hepatocellular carcinoma was used as positive control. Conclusions: Our results reveal definite presence of HBV in the synovium which may be involved in the pathogenesis of local lesion and exacerbate disease progression in RA patients with CHB. Acknowledgements: This work was supported by National Natural Science Foundation of China (grant No. 81671612 and 81601427), Guangdong Natural Science Foundation (grant No. 2016A030313307 and 2016A030313307) and Fundamental Research Funds for the Central Universities (grant No. 17ykjc12). Disclosure of Interest: None declared